SOLUSI ALTERNATIF PENYAMPAIAN INFORMASI DENGAN TOLERANSI WAKTU TUNDA UNTUK PENGGUNA LAYANAN KOMUNIKASI DATA PADA VEHICULAR NETWORK - Nurul Salsabila Wardhani; Melky Sedek Hosea Halim; Ngurah Indra ER (Jurnal SPEKTRUM, 2023)
Data demand from personal mobile devices over cellular networks is rapidly increasing. For time-delay tolerant data, the use of paid technology is inefficient. As an alternative for time-delay tolerant data delivery, opportunistic networks are emerging as an effective infrastructure-less communication model. Before it can be used as an alternative solution, it is necessary to analyze the performance of using opportunistic networks, especially the basic routing patterns used. This research analyzes the performance of routing patterns in opportunistic networks by utilizing inter-vehicle networks as mobile nodes in Denpasar City. Two basic routing patterns, namely epidemic and spray and wait, are simulated using The ONE Simulator into two scenarios including a scenario of increasing the average vehicle and a scenario of increasing the buffer size. The simulation results show that in the inter-vehicle network utilization, epidemic routing pattern is superior to spray and wait in terms of delivery probability and average latency, but when assessing in terms of overhead ratio, spray and wait routing pattern can provide lower results. This shows that the epidemic routing pattern is suitable for systems that do not care about high resource utilization.